Kinetic and thermodynamic studies of Cu(II) adsorption onto calcium phosphate - Dogan, Ozlem; Bodur, Basra; Inan, Gozde (DESALINATION PUBL, 2018)
Adsorption of Cu(II) from aqueous solutions by calcium phosphate powders, which were produced by wet chemical synthesis has been studied. The equilibrium data were analyzed using Langmuir and Freundlich isotherm models. It was determined that the Langmuir isotherm fitted well the adsorption isotherm of Cu(II). As a result of the experiments performed, the maximum adsorption capacities of powders increased from 13.76 mg/g to 19.92 mg/g when the adsorbent production temperature decreased from 70 degrees C to 25 degrees C. Thermodynamic data revealed that the adsorption process was spontaneous and endothermic. Adsorption kinetics data were tested using pseudo-first-order, pseudo-second-order, and intraparticle diffusion models. The pseudo-second-order model is the most convenient model to represent the adsorption kinetic.
Keywords: Adsorption isotherm; Kinetics; Thermodynamics; Heavy metals; Calcium phosphate; Copper; WASTE-WATER TREATMENT; HEAVY-METAL IONS; AQUEOUS-SOLUTION; ACTIVATED CARBON; HYDROXYAPATITE NANOPARTICLES; REMOVAL; EQUILIBRIUM; COPPER(II); ADSORBENTS; PARAMETERS; Engineering; Water Resources